2012
DOI: 10.1128/jb.06519-11
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Proteomic Adaptation of “Aromatoleum aromaticum” EbN1 to Low Growth Rates in Benzoate-Limited, Anoxic Chemostats

Abstract: ؊1 ) growth rates. A positive correlation to growth rate was observed for cellular parameters (cell size, and DNA and protein contents). The free energy consumed for biomass formation steadily increased with growth rate. In contrast, the energy demand for maintenance increased only from low to med and then remained constant until high . The most comprehensive proteomic changes were observed at low compared to high . Uniformly decreased abundances of protein components of the anaerobic benzoyl coenzyme A (benzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 83 publications
1
39
0
Order By: Relevance
“…In carbon-and energy-limited environments, constitutive expression increases an organism's capacity to react quickly to transiently available nutrients (30). For example, in what they termed "catabolic preparedness," Trautwein et al (31) recently demonstrated that Azoarcus sp. EbN1 expressed a large number of proteins involved in anaerobic hydrocarbon degradation despite the absence of their respective substrates from the growth medium.…”
Section: Discussionmentioning
confidence: 99%
“…In carbon-and energy-limited environments, constitutive expression increases an organism's capacity to react quickly to transiently available nutrients (30). For example, in what they termed "catabolic preparedness," Trautwein et al (31) recently demonstrated that Azoarcus sp. EbN1 expressed a large number of proteins involved in anaerobic hydrocarbon degradation despite the absence of their respective substrates from the growth medium.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane proteins were prepared as described by Trautwein and colleagues () and subjected to separation according to molecular mass on 25 × 30 cm, 12.5% SDS gels (Bio‐Rad, Munich, Germany). Each sample lane was divided into 15 gel slices, and each slice cut into smaller pieces (about 1 mm) prior to washing, reduction, alkylation and tryptic digest.…”
Section: Methodsmentioning
confidence: 99%
“…For shotgun analysis, total protein prepared individually from three biological replicates per substrate condition was digested and subjected to nanoLC-ESI-MS/MS as described (Trautwein et al, 2012).…”
Section: Proteomic Analysismentioning
confidence: 99%